2019
DOI: 10.1149/2.0771910jes
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comments on E. Huttunen-Saarivirta et al., “Kinetic Properties of the Passive Film on Copper in the Presence of Sulfate-Reducing Bacteria” [J. Electrochem. Soc., 165, C450 (2018)]

Abstract: The Comments by Martino et al. 1 on the original manuscript 2 criticize our interpretation of the existence and properties of the Cu 2 S barrier layer of the passive film that forms on the surface of copper in SRB-bearing groundwater at 10°C. First, it is necessary to recognize that this discussion involves two forms of copper, which we refer to as "pure copper (P-Cu)" (nominally > 99.999%) and "oxygen-free phosphorous copper (OFP-Cu)". P-Cu has been used in the majority of our work [3][4][5][6] with only some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Some counterarguments have been raised about this description, suggesting the films may be passive, [ 33 ] and these questions have been clarified, [ 34 ] rebutted, [ 35 ] and further debated. [ 36 ] The most recent experimental and mechanistic analyses do not support the existence of a barrier film [ 37 ] ; thus, the description of a passive sulfide film does not enter safety arguments for SKB [ 38 ] or the NWMO. Slow diffusion of trace sulfide is considered to be the most likely cause of long‐term copper corrosion via general corrosion rather than pitting.…”
Section: Program Context: the Evolution Of The Nwmo Proof Test Plan (mentioning
confidence: 99%
See 1 more Smart Citation
“…Some counterarguments have been raised about this description, suggesting the films may be passive, [ 33 ] and these questions have been clarified, [ 34 ] rebutted, [ 35 ] and further debated. [ 36 ] The most recent experimental and mechanistic analyses do not support the existence of a barrier film [ 37 ] ; thus, the description of a passive sulfide film does not enter safety arguments for SKB [ 38 ] or the NWMO. Slow diffusion of trace sulfide is considered to be the most likely cause of long‐term copper corrosion via general corrosion rather than pitting.…”
Section: Program Context: the Evolution Of The Nwmo Proof Test Plan (mentioning
confidence: 99%
“…Rather, the corrosion product will remain porous, such that incoming sulfide will be able to continuously react at the copper surface. Some counterarguments have been raised about this description, suggesting the films may be passive, [ 33 ] and these questions have been clarified, [ 34 ] rebutted, [ 35 ] and further debated. [ 36 ] The most recent experimental and mechanistic analyses do not support the existence of a barrier film [ 37 ] ; thus, the description of a passive sulfide film does not enter safety arguments for SKB [ 38 ] or the NWMO.…”
Section: Program Context: the Evolution Of The Nwmo Proof Test Plan (mentioning
confidence: 99%
“…Passive film properties are described in terms of the point defect model and evidence for film breakdown and pitting have been presented. [ 34–39 ] The observation of a levelling off of the anodic current with increasing potential during cyclic voltammetry is consistent with passive behaviour, [ 37 ] although the observed current is the same on the forward and reverse potential scans, which would not be expected if a passive film had been formed on the forward scan. [ 41 ] Martino et al [ 41 ] also suggested that the reported film breakdown events [ 34,36 ] were instead the onset of rapid anodic dissolution of copper as CuCl 2 − species through a porous Cu 2 S film.…”
Section: Canister Evolutionmentioning
confidence: 63%
“…One example of this difference between laboratory and repository conditions relates to the properties of the Cu 2 S formed on copper in sulphide‐containing environments. There has been a recent debate in the literature about whether these films should be classified as passive [ 34–39 ] or porous. [ 1–4, 40,41 ] Although there is no strict definition of a passive versus a porous film, the important distinction here is that passive films could be subject to localised breakdown and pitting, [ 34–37 ] whereas a copper surface covered by a porous film would tend to corrode relatively uniformly.…”
Section: Canister Evolutionmentioning
confidence: 99%
“…[ 40–43 ] While some debate persisted about the nature of the copper sulfide films formed below this proposed concentration threshold, the most recent data produced on this subject affirms that passive films are not expected. [ 44–49 ] Furthermore, in a DGR like scenario, diffusion of sulfide to the UFC surface would be very slow which further supports the formation of porous corrosion products. [ 40 ] Therefore, in terms of the NWMO corrosion allowance, only slow uniform sulfide‐induced corrosion resulting from far‐field production of sulfide is accounted for.…”
Section: Corrosion Programsmentioning
confidence: 99%